THE ROLE OF FIGURATIVE LANGUAGE IN PERSUASIVE WRITING - Maripov Jalolxon Kamoliddin oʻgʻli; Qodirova Iroda Ulug`bek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Figurative language is a crucial part of persuasive writing because it appeals to the audience’s emotions, imagination, and intellect, which increases the impact of arguments. This article explores the many types of figurative language, including personification, similes, metaphors, and hyperbole, and how they can enhance the persuasiveness of writing. Figurative language not only enhances the content but also gives authors the ability to more successfully impact their audience by establishing emotional connections, making difficult concepts understandable, and crafting memorable phrases. This investigation shows how ordinary writing can be effectively persuaded through the thoughtful use of figurative language.